A new therapy to alleviate the inflammatory injury of piglet intestine caused by short-distance transportation——music - Qin Fu; Bin Bai; Sitong Zhou; Yunlong Zhao; Yue Yang; Xiaohong Zhang; Xuanning Liu; Mengyao Wu; Wenzhong Zhao; Jun Bao; Honggui Liu (PLoS ONE, 2025)
The purpose of this study was to explore whether music can reduce stress in animals by regulating the activity of the hypothalamus pituitary adrenal cortex (HPA) axis and reducing the concentration of cortisol. The control group was not played with any music or mechanical noise, the music group played music before and during transport, and the noise group played noise before and during transport as a positive control. The results showed that after two-hours of transportation, the concentrations of adrenocorticotropic hormone and cortisol in the music group were lower than that in the control and the noise groups, while the cortisol level in the noise group was higher than that in the music and the control groups. Plasma concentrations of D-lactic acid and diamine oxidase in the music group were lower than those in the control group and the noise group, and the noise group was higher than the control group. In addition, the concentrations of jejunal inflammatory factors interleukin-6 and interleukin-8 in the music group were lower than those in the control group and the noise group, but there was no difference of interleukin-12 in the three groups. However, there was no significant difference in Illinois-6, Illinois-12 and INF-γ between the noise group and the control group. The contents of reactive oxygen species, malondialdehyde and glutathione peroxidase in the music group had no changes compared with those in the control group, while the contents of reactive oxygen species and malondialdehyde in the noise group were higher than the control and the music groups, and the content of glutathione peroxidase was decreased. Compared with the music group, differently expressed genes analysis also showed that the mRNA expression level of inflammatory genes in the jejunum of the music group’ piglets decreased. In addition, compared with the music group, some Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways related to inflammation were highly expressed in the control group. In conclusion, our results showed that musical stimulation can reduce the inflammatory response of piglets caused by transportation by reducing the activity of HPA axis. Noise increased the activity of HPA axis, which aggravated the intestinal damage of piglets and caused intestinal oxidative damage